Gametophyte morphology of Acrostichum aureum and A. danaeifolium (Pteridaceae) - Castrejón-Varela, Alejandra; Pérez-García, Blanca; Mendoza-Ruiz, Aniceto; Espinosa-Matías, Silvia (Revista de Biología Tropical, 2018)
Acrostichum is a pantropical genus and has four species, two of which occur in the Neotropics, A. aureum and A. danaeifolium. In Mexico, A. danaeifolium grows further in land wet soils and is much more common than A. aureum, which is typically found in brackish or saline habitats near the coast, and is restricted to coastal saline mangrove communities. The purpose of this paper was to describe and compare the morphogenesis of the sexual phase of A. aureum and A. danaeifolium for systematic purposes. For this, spores of each species were sown in Petri dishes with agar, previously enriched with sterilized Thompson's medium. To avoid contamination and dehydration, the dishes were kept in transparent plastic bags under laboratory conditions. For the micro-morphological observation with SEM, the gametophyte development phases were fixed in FAA with 0.8 % sucrose for 24 h. Photomicrographs of spores, development stages of gametophytes and young sporophytes were observed with scanning electron microscope Jeol JSM5310-LV. Our results showed that the spores of both species are triletes, globose and positive photoblastic. Germination is Vittaria-type; the germinate filaments are short and uniseriate (5 to 7 cells), and prothallial development is Ceratopteris-type. The adult gametophytes of both species have asymmetrical wings. Adult gametophytes in culture are cordiform-spatulate. Antheridia have a broad basal cell, an annular cell, and an asymmetric opercular cell. Archegonia have short necks and four triangular cells at the mouth of the neck. The first leaf of the sporophyte is lobed, with dichotomous veins and anomocytic stomata. The gemmae are formed in adult gametophytes in both species. The development of the gametophyte of A. aureum, A. danaeifolium and A. speciosum share many similarities such as the development of a lateral meristem, asymmetric nature of the mature prothallus, lack of hairs on the prothallus, and undivided asymmetrical opercular antheridia morphology. The genus Acrostichum is the sister group of Ceratopteris, another genus of aquatic ferns; they differ in the antheridium morphology, Acrostichum has an asymmetric opercular cell and Ceratopteris shows an undivided cap cell, but the notable difference is the sporophyte morphology.